The Challenge of the Millennial Generation of Muslims: Between the Dilemma of Progress and Setbacks - Alam, Syariful (KnE Social Sciences, 2022)
The millennial Muslim generation has a striking, creative, energetic, and optimistic existence. But not all Muslims today are part of this millennial generation. Some groups refuse, support, or mediate. Modernity, in essence, is no longer a symptom that must be opposed, fought, and destroyed; on the contrary, millennial Muslims believe that faith and modernity can collaborate, go hand in hand, and complement each other. Muslim societies are forced to make changes in mindset and reform their communities so that they can improve their backwardness and are finally able to make many positive contributions. Science, technology, and information are vital parts of progress that have dominated all aspects of social life, even religion. The rapid freedom of information can be taken as an opportunity, while it can also become a challenge for Muslim societies in facing the positive and negative impacts that attack internally and externally, which will cause major changes in influencing the creed, association, and thoughts that slowly damage the teachings of Islam. So it is necessary to have a critical attitude and moderate understanding in facing challenges amid the current of modernity. Keywords: millennial, generation, Muslim, religion, modern